Academic Stress in the Final-Year Students: Do Religiosity and Religious Coping Matter? - Eko Sujadi (Department of Guidance and Counseling, FIP, Undiksha, 2022)
Final-year students are often faced with stressful conditions. They have to complete all the academic demands that are so many. This study aimed to examine the direct effect of religiosity and religious coping on academic stress and the mediating effect of religious coping on the relationship between religiosity and academic stress. A total of 191 final-year students at one of the universities in Indonesia participated in filling out the College Student Stress Scale, Religiosity Scale among Muslims and The Brief RCOPE. Structural model testing using the structural equation model through the SmartPLS 3.0. The results showed a direct negative effect of religiosity and religious coping on academic stress. In addition, the relationship between religiosity and academic stress is mediated by religious coping. There needs to be an effort to maximize the process of academic guidance carried out by academic supervisors. Prevention and intervention of academic stress can also be done through guidance and counselling services carried out by professional counsellors. Final-year students also need social support from those closest to them.